3D explicit simulation of bearing failure in metal–composite bolted joints. (15th March 2022) - Rouhi, Mohammad S.; Ramantani, Dimitra; Tay, Tong Earn
Abstract: Hybrid bolted joints between composite materials and metals are an example of composites' sensitivity to notches. The current research paper presents an experimental test setup on single-lap shear bolted joints of a unidirectional (UD) composite laminate with steel plate exposed to a tensile load. A 3D explicit finite element (FE) simulation is developed using ABAQUS/Explicit and a 3D physically-based progressive damage model in the VUMAT subroutine. The model can identify the locations of delamination represented by the fully damaged plies among other degrading properties. Then "damage and cohesive" contact surfaces are defined in the respected damaged plies, for the material interface, to simulate interlaminar damage and delamination. The predicted failure load was significantly influenced by the combination of a 3D physically-based progressive damage model and damage and cohesive surfaces. The combined model can reproduce with accuracy the experimental load–displacement test curves up to the point where bearing damage occurs. Experimental results using DIC measurement are presented to demonstrate the feasibility of the methodology. The study shows that numerical models can be used to help in the stiffness and strength design of the bolted joints of composites and metals, but further improvements are necessary to predict the energy absorption.